Effects of 1,2-ethanedithiol concentration on performance improvement of quantum-dot LEDs - Nguyen, Huu Tuan; Ryu, Shin Young; Duong, Anh Tuan; Lee, Soonil (RSC Advances, 2019)
We report systematic efficiency variations of green-emitting CdSe@ZnS quantum-dot (QD) LEDs (QLEDs) in response to in situ treatments with 1,2-ethanedithiol (EDT) solutions at various concentrations. The main effect of in situ EDT treatment on a QD layer spin-coated onto a ZnO layer was vacuum-level shift due to dipole moments on the surface of the QD layer and at the interface between QD and ZnO layers. Competing contributions of these dipole moments were responsible for changes in energy level configurations and, accordingly, electron and hole barriers that resulted in discrepancies in electron- and hole-current variations. QLED efficiency was best when treated with an EDT solution of 4 mM, attributable to the largest increase in the hole- to electron current ratio. The maximum luminous yield of the 4 mM EDT-treated QLED was 5.43 cd A-1, which is 10 times higher than that of an untreated device. Furthermore, the luminous yield of this treated device remained as high as 2.56 cd A-1 at a luminance of 500 cd m-2
Keywords: CdSe-ZnS; Electron currents; Hole barrier; Hole current; In-situ treatment; Main effect; Vacuum level shift; ZnO layers